O processo de inclusão de estudantes especiais no ensino regular: o ideal e a realidade - Oliveira, Ivana Corrêa Tavares (2016)
The 2014 School Census show that students with disabilities represent 2.83% of all students enrolled in regular classes in the early years of elementary school while in high school the rate is 0.70%. The proportion of students who enroll in high school does not follow the entry into elementary school. Given this evasion, there are questions about the supply and quality of education provided to students with disabilities. This paper aims to discuss the inclusion of students with disabilities in regular education in Brazil, questioning its principles from a dialogue with the inclusion policy adopted by more advanced countries. As a complement, we intend to articulate the literature with the analysis of fragments of pedagogical interventions applied to students with disabilities enrolled in regular education, in the Room Care and Support Inclusion (RCSI). This is a case study, in a qualitative research approach, which has as its subject the teacher of RCSI and some of her/is students. The results indicate that, between legislation and its implementation, there are obstacles to the full integration of students with disabilities in the Brazilian regular education: the number of student per class, the shortage of school life assistants or interns to help the teacher, the lack of dialogue with other areas for the planning of this public’s care and also the few opportunities for teacher training